Legal Protection of Workers' Rights for Victims of Workplace Accidents: A Cross-National Comparative Analysis in the Context of Worker Welfare - Sahda Saraswati Akbar; Rianda Dirkareshza (Journal of Law, Politic and Humanities, 2024)
Workers' rights to occupational safety are defined as rights that must be considered by all countries as stated in article 23 of the Universal Declaration of Human Rights. Through this, the author is interested in conducting research as a form of achieving better worker welfare and also aims to provide insight for policy makers to improve and develop regulations related to worker safety and health. This study uses a comparative method that compares regulations in Iceland, Canada, Belgium, Singapore, Australia with regulations in Indonesia using a legal research approach and a conceptual approach. The novelty in this study is to conduct a comparative study of the six countries in achieving worker welfare through aspects of worker health and safety. However, of course Indonesia needs to make other considerations in determining regulations or policies that will be adopted through implementation in other countries.